Nickel contamination of laterite soil by hydraulic fracturing flowback water: Geochemical behaviour and policy implications. (7th August 2020) - Wang, Li; Yang, Xinxin; Liu, Weijiang; Liu, Mingzhu; Chen, Honghan
Abstract: Accidental flowback water spills can cause serious soil pollution. Nickel (Ni) is one of the common heavy metal components in flowback water. However, the behaviour and mechanism of Ni in flowback water in dolomite‐derived laterite soil are poorly understood. In this study, laterite soils were selected from a Cambrian dolomite strata in China. Column experiments and synthetic flowback water were used to investigate the mobilization of Ni. The results indicated that Ni behaviour was affected by the ionic strength and soil carbonate content. In laterite soil with a low dolomite content, as the pH of the solution decreases and the ionic strength increases, the positive charge on the soil surface increases, and chlorocomplexation reactions and competitive adsorption are enhanced, ultimately promoting the migration of Ni. The recovery rate increased from 10% to 61% for the soil with 3% dolomite. In laterite soil with a high dolomite content, the formation of Ni‐Ca carbonate double salt and Ni‐Al‐‐layered double hydroxides severely inhibits the migration of Ni. The maximum recovery rate was 13%. A multireaction and transport model that accounts for linear equilibrium, nonlinear kinetics and irreversible kinetic mechanisms was effective in describing the breakthrough curves for the two laterite soil columns and capturing the effect of the solution composition on Ni transport. These results are helpful in understanding and predicting Ni's fate in the flowback water accidentally spilled into the surrounding laterite soil area, and provide references for soil pollution management policies under shale gas development.